Draft environmental impact statement, proposed federal/state oil and gas lease sale, Beaufort Sea - United States. Bureau of Land Management ([Washington, D.C.] : U.S. Bureau of Land Management, 1979)
Includes bibliographical references Mode of access: Internet.